The role of government in developing sustainable SMEs in the construction sector in the Free State province - Motsetse, Makhaesa Jeffrey (University of the Free State, 2015)
The objective of the study is to determine the role of government in developing sustainable SMEs in the construction sector in the Free State province. The owners and managers who are on Grading 2 to 7 as per Construction Industry Development Board (CIDB) in the construction sector were the target population. The number of businesses that are failing in their first years of establishment is high, and the rate of unemployment is still high despite government intervention. If government is playing a role in assisting SMEs, to determine whether it is addressing the main challenges that are affecting the growth of small businesses due to the number of companies that are failing is increasing. The construction sector is also affected by the number of businesses that are failing or liquidated, which is affecting employment negatively, as the sector employs a number of workers who are unskilled. An empirical research was conducted using quantitative approach and non-probability, stratified sampling technique. A total of 100 questionnaires were distributed to the owners and managers of the construction companies in the Free State that are operating on Grading 2 to 7. The total of 84 questionnaires were returned, representing 84% of the total that were distributed The result shows that 96% of the respondents did not receive any funding from government, while only 4% received funding. It is also revealed that 64% of the respondents are not participating in the contractor development programme, and only 36% of them are participating. The level of education or training is low, as 36.90% attended the workshop on tendering.
Dissertation (MBA (Business Administration))--University of the Free State, 2015
Keywords: Government intervention; SME; Construction sector